Medical devices and systems - Bronzino, Joseph D., 1937- (Electrical engineering handbook series., 2006)
Already referred to as "the bible of biomedical engineering," the third edition of The Biomedical Engineering Handbook is even more vast in its scope and depth than the previous two editions. Ranging from the theoretical to state-of-the-art applications, this edition includes so much new and updated material that it has expanded from two volumes into a three-volume set. The author again employs an interdisciplinary approach to the field. The second volume, Medical Devices and Systems has been updated to reflect the most recent advances in both research and practice in all pertinent fields. New.